Multiple Objective Analysis of Input-Output Models for Emergency Management - Kananen, Ilkka; Korhonen, Pekka; Wallenius, Jyrki; Wallenius, Hannele (Operations research, 1990)
This paper shows how a visual, interactive, dynamic multiple objective linear programming decision support system can effectively be used for analyzing input-output models. We have applied our approach to studying the quantitative effects of economic or political crises to the Finnish economy. Examples of such crises are nuclear power plant accidents, trade embargoes, and international conflicts. An input-output model of the Finnish economy with 17 industries (sectors) is employed. Our system has been implemented on a microcomputer and is being used by the National Board of Economic Defense. Several typical case situations are discussed.